Emissões de poluentes em centrais hidrelétricas: aspectos técnicos, econômicos e ecológicos - Siqueira, Ricardo Barbosa Posch [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The reservoir of the hydropower plants contributes to increased emissions of greenhouse gases (GHG), emitting carbon dioxide (CO2) and methane (CH4), that are harmful gases to the global warming. This work aims to develop a methodology that assess the hydroelectric powerplants on the environmental aspect and its ecological efficiency. Analyze the hydroelectric to the ecological efficiency considers the pollution indicator to determine how polluter is a process of electricity generation. Initially, used a reservoir model where consider the operating system of the plant, correlating it to the variable volume, flooding area, water quality and load of the reservoir. The methodology is based on the static / computational model using a software tool (Excel®) and considering a reservoir whose characteristic of the section and volume are related to a trapezoidal plane figure. The study considers the characteristics of the hydroelectrics Itaipu and Tucuruí, which can be obtained the average emissions of CO2 and CH4. The equations are developed to tC and tCO2 equivalent emissions, which support in the development and validation of the model and of the environmental impact study, and in the determination of the hydropower ecological efficiency. Those equations are written as a function of the reservoir load and water quality index, that considers dissolved oxygen saturated (ODSat%). To determine the load of reservoir is considered an electrical analogy (Resistor-Capacitor Circuit), where the reservoir is equivalent to a capacitor and the turbine equivalent to electrical resistance. In the environmental analysis, it is used the equivalent emission of CO2 (tCO2eq) to determine the pollution indicators and the ecological efficiency of the hydroelectric plant, including the Global Warming Potential (GWP). Concludes with the developed model that the ... (Complete abstract click electronic access below)

Os reservatórios das Centrais Hidrelétricas contribuem para o aumento dos Gases de Efeito Estufa (GEE), emitindo dióxido de carbono (CO2) e metano (CH4), que são nocivos para o aquecimento global. Esse trabalho de tese tem como objetivo desenvolver uma metodologia que permita avaliar as hidrelétricas acerca do aspecto ambiental e de sua eficiência ecológica. Analisar uma planta hidrelétrica sob o ponto de vista da eficiência ecológica implica em determinar o indicador de poluição para verificar quão poluidor é o processo de geração de eletricidade da usina. Inicialmente, utiliza-se um modelo de reservatório que considera o regime operacional da usina, correlacionando-o às variáveis de volume, área alagada, qualidade da água e carga do reservatório. A metodologia baseia-se em modelo estático/computacional, utilizando o Programa Excel® e considerando um reservatório cuja característica de seção e volume é o de uma figura plana trapezoidal. O estudo considera as características das usinas hidrelétricas de Itaipu e de Tucuruí, das quais é possível obter as emissões médias de CO2 e CH4. Desenvolvem-se as equações para a determinação das emissões equivalentes de tC e tCO2, as quais auxiliam no desenvolvimento e validação do modelo e do estudo do impacto ambiental e na determinação da eficiência ecológica da usina hidrelétrica. Essas equações são escritas em função da carga do reservatório e do índice de qualidade da água, que considera o oxigênio dissolvido saturado (ODSat%). Para a determinação da carga do reservatório, considera-se a analogia elétrica (Circuito Resistor-Capacitor), onde o reservatório é considerado equivalente a um capacitor e a turbina hidráulica equivalente a uma resistência elétrica. Na análise ambiental, utiliza-se a emissão equivalente de CO2 (tCO2eq) para ... (Resumo completo, clicar acesso eletrônico abaixo)
GHG emissions of power plants: technical, economical and ecological aspects
Keywords: Usinas hidrelétricas; Água - Qualidade; Efeito estufa (Atmosfera); Análise econômico-financeira; Eficiência do uso da água; Hydroelectric power plants